Pathological Features of Tumors of the Nervous System in Hereditary Cancer Predisposition Syndromes: A Review. Issue 3 (8th March 2021) - Tadros, Saber; Kondrashov, Aleksei; Namagiri, Sriya; Chowdhury, Ashis; Banasavadi-Siddegowda, Yeshavanth Kumar; Ray-Chaudhury, Abhik
Abstract: Hereditary cancer predisposition syndromes (HCS) become more recognizable as the knowledge about them expands, and genetic testing becomes more affordable. In this review, we discussed the known HCS that predispose to central and peripheral nervous system tumors. Different genetic phenomena were highlighted, and the important cellular biological alterations were summarized. Genetic mosaicism and germline mutations are features of HCS, and recently, they were described in normal population and as modifiers for the genetic landscape of sporadic tumors. Description of the tumors arising in these conditions was augmented by representative cases explaining the main pathological findings. Clinical spectrum of the syndromes and diagnostic criteria were tabled to outline their role in defining these disorders. Interestingly, precision medicine has found its way to help these groups of patients by offering targeted preventive measures. Understanding the signaling pathway alteration of mammalian target of rapamycin (mTOR) in tuberous sclerosis helped introducing mTOR inhibitors as a prophylactic treatment in these patients. More research to define the germline genetic alterations and resulting cellular signaling perturbations is needed for effective risk-reducing interventions beyond prophylactic surgeries.